EFISIENSI PENGELOLAAN PERSEDIAAN STOK MENGGUNAKAN METODE SAFETY STOCK DI KAKI NAGA JEPARA - Putri, Natasya; Leni Amrita; Arina Zulfa; Danang Mahendra; Joko Minardi (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Inventory management is crucial for any business to ensure smooth operations and customer satisfaction. This study investigates the efficiency of inventory management using the Safety Stock method at Kaki Naga Jepara. The research aims to determine how this method can help maintain optimal inventory levels, reduce stockouts, and minimize carrying costs. Using a combination of quantitative data analysis and case study methodology, the results indicate that the Safety Stock method significantly improves inventory management efficiency by providing a buffer against demand variability and lead time fluctuations.